Clinical outcome and left atrial function after left atrial roof ablation using the cryoballoon technique in patients with symptomatic persistent atrial fibrillation. (1st October 2019) - Akkaya, Ersan; Berkowitsch, Alexander; Rieth, Andreas; Erkapic, Damir; Hamm, Christian W.; Neumann, Thomas; Kuniss, Malte
Abstract: Introduction: There are no data concerning clinical outcome and left atrial (LA) function after LA roof ablation using a second-generation cryoballoon (CB) for treatment of persistent atrial fibrillation (AF). Here, we report the first follow-up results after pulmonary vein isolation (PVI) plus LA roof ablation with the CB technique in patients with symptomatic persistent AF. Methods and results: We enrolled 107 consecutive patients who underwent CB ablation at our institution with the aim of PVI and bidirectional conduction block across the LA roof. Clinical success was defined as freedom from >30-s recurrence of AF, atrial flutter, or atrial tachycardia after a 3-month blanking period. Follow-up data were collected during outpatient clinic visits. LA volume, LA emptying fraction, and LA expansion index (parameters of LA function) were evaluated by echocardiography before and 3 months after ablation. PVI was achieved in all patients, and bidirectional conduction block was verified in 91.6%. Median follow-up duration was 31 (interquartile range 11/44) months. PVI plus LA roof ablation was sufficient to restore and maintain sinus rhythm in 72.9% ( n  = 78) of patients. The overall complication rate was 1.8%. LA volumes decreased significantly after ablation ( P  < 0.05), whereas total LA emptying fraction ( P  = 0.25) and LA expansion index ( P  = 0.32) were preserved within the 3-month follow-up. Conclusions: LA roof ablation combined with PVI using the CB technique is a safe and effective adjuvant treatment with a promising midterm outcome and preserved LA function 3 months after ablation. Highlights: Left atrial roof ablation using second-generation cryoballoon was safe and effective. Pulmonary vein isolation plus roof line ablation showed a promising outcome. Left atrial function was not impaired during short-term follow-up.